Answers

The Brainliest Answer!
2015-03-11T12:46:36+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let x =  \sqrt{6+ \sqrt{6+ \sqrt{6+} \sqrt{6+........}  } }

Squaring on both sides

x² = 6 +   \sqrt{6+ \sqrt{6+ \sqrt{6+} \sqrt{6+........} } }

⇒x² = 6 + x

⇒ x² - x - 6 = 0

⇒ (x-3)(x+2) = 0

⇒ x = 3 or x = -2

Ignoring negative value,,

x = 3

 \sqrt{6+ \sqrt{6+ \sqrt{6+} \sqrt{6+........} } } = 3
2 5 2
sir how x2=6+x
As the term √6+√6+√6+√6........... is an infinite term....so after squaring on both sides...it remains 6 + √6+√6+√6+√6...............so it is 6 + x on RHS
Thnx expert..please answer my other question